Impact evaluation study for Egypt's Takaful and Karama cash transfer program: Part 1: Quantitative report - Breisinger, Clemens; Gilligan, Daniel O.; Karachiwalla, Naureen; Kurdi, Sikandra; El-Enbaby, Hoda; Jilani, Amir Hamza; Thai, Giang (International Food Policy Research Institute, 2018)
This report of the evaluation study provides a greater focus on measuring the impact of the larger Takaful program and also attempts to measure the impact of the much smaller Karama program. In addition, IFPRI will conduct a qualitative assessment of the Takaful and Karama program focused on learning about the experience with the program among the poorest beneficiary households. This qualitative assessment will also draw lessons from the quantitative survey to provide another report on the experience of very poor households. The remainder of this report is organized as follows Chapter 2 provides an overview of the Takaful and Karama Program. Chapter 3 summarizes the impact evaluation design. Chapter 4 describes the evaluation survey and sample. Chapter 5 provides context for the program by using the survey data to summarize the characteristics of beneficiary and non-beneficiary households and describe beneficiaries’ experience with program implementation. Chapter 6 presents the impact estimates for Takaful and Chapter 7 the estimates for Karama. Chapter 8 uses data from a separate representative sample of households collected during the survey to assess the targeting performance of the program. Chapter 9 concludes and discusses implications for social policy in Egypt.